Mastering the art of French eating : lessons in food and love from a year in Paris - Mah, Ann (Pamela Dorman Books / Viking, 2013)
"The memoir of a young diplomat's wife who must reinvent her dream of living in Paris-one dish at a time When journalist Ann Mah's diplomat husband is given a three-year assignment in Paris, Ann is overjoyed. A lifelong foodie and Francophile, she immediately begins plotting gastronomic adventures à deux. Then her husband is called away to Iraq on a year-long post-alone. Suddenly, Ann's vision of a romantic sojourn in the City of Light is turned upside down. So, not unlike another diplomatic wife, Julia Child, Ann must find a life for herself in a new city. Journeying through Paris and the surrounding regions of France, Ann combats her loneliness by seeking out the perfect pain au chocolat and learning the way the andouillette sausage is really made. She explores the history and taste of everything from boeuf Bourguignon to soupe au pistou to the crispiest of buckwheat crepes. And somewhere between Paris and the south of France, she uncovers a few of life's truths. Like Sarah Turnbull's Almost French and Julie Powell's New York Times bestseller Julie and Julia, Mastering the Art of French Eating is interwoven with the lively characters Ann meets and the traditional recipes she samples. Both funny and intelligent, this is a story about love-of food, family, and France"--